Vegetation analysis and culturable endophytic fungal associations in agarwood from different forest types in Marumana, Papua, Indonesia - YENNY YENDRI SALOSA; TUTIK KUSWINANTI; INDAH RAYA; EKO AGUS MARTANTO (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Salosa YY, Kuswinanti T, Raya I, Martanto EA. 2025. Vegetation analysis and culturable endophytic fungal associations in agarwood from different forest types in Marumana, Papua, Indonesia. Biodiversitas 26: 4874-4885. Aquilaria filaria is a tree species valued for producing agarwood, a resinous heartwood formed in response to pathogenic fungal infections. Despite its ecological and economic significance, detailed studies on the habitat ecology of A. filaria in Papua remain scarce. This study investigated variation in vegetation stands containing A. filaria and identified pathogenic fungi associated with its infection. Fieldwork was conducted from January to March 2023 across 40 plots (50 × 50 m) established along two 1-km transects designed to capture gradients of human disturbance. Vegetation was surveyed using the Braun-Blanquet method and analyzed by TWINSPAN classification. Fungal isolation from infected stems (50% of representative A. filaria trees per plot) employed a modified direct-plating method on half-strength potato dextrose agar, with taxonomic identification based on morphological keys. A total of 97 plant species and 198 A. filaria individuals were recorded, yielding 600 wood fragments across three disturbance gradients. Dominant families included Euphorbiaceae and Moraceae. Pathogenicity tests revealed four major fungal genera: Trichoderma, Fusarium, Penicillium, and Aspergillus niger. Colonization rates increased from 70% in undisturbed to 90% in heavily disturbed sites, while fungal load, expressed as colony counts per fragment, rose from 1.76 to 2.96 across the same gradient. Diversity, measured by the Shannon-Wiener Index, declined from 1.08 in undisturbed to 0.68 and 0.67 in moderately and highly disturbed sites, respectively. These findings provide new insights into how forest disturbance reshapes vegetation structure and fungal assemblages in A. filaria habitats, highlighting the need to preserve forest complexity while balancing ecological resilience with economic goals.